Analisis gugus fungsi nanopartikel magnetite Fe3O4 yang disintesis hijau menggunakan ekstrak moringa oleifera - Firdaus, Fazri; Tabrani, Rizqi A’mal Hibatullah; Saefullah, Asep; Antarnusa, Ganesha (Jurnal Teras Fisika: Teori, Modeling, dan Aplikasi Fisika, 2024)
A study was conducted to analyze the functional groups in green synthesized (GS) Fe3O4 samples using Moringa Oleifera (MO) and black iron oxide (Fe3O4) nanoparticles using FTIR-Spectroscopy. Functional group analysis of the samples was carried out to ascertain whether there was any difference in the formation of MNPs from the use of MO, molecular bonds were observed using FTIR spectra. The presence of magnetite nanoparticle absorption peaks showed two vibrational bands in the range of wave numbers 596-642 cm-1, which correspond to the stretching vibrations of the M-O (metal-oxide) bond. The absorption around 578 cm-1 corresponds to stretching vibrations on the tetrahedral sites of the metal (Fetetra-O). The formation of GS-Fe3O4 is strongly confirmed by the presence of characteristics similar to conventional Fe3O4 in the range of wave numbers 1391, 1633 and 2318 cm-1, which represent stretching vibrations of C=O, N-H, C=O chemical bonds, and another absorption peak at wave number 3167 cm-1 corresponding to vibrations of O-H (hydroxyl) groups.